Prevalence of Anxiety and Depression in Hemodialysis Patients at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar: A Descriptive Study - Ni Nyoman Ayu Trsinawati; Diah Pritasari Jeger; Yenny Kandarini (MEDICINUS, 2026)
Background: Patients with chronic kidney disease (CKD) undergoing hemodialysis (HD) often experience substantial physical and psychological burdens, including anxiety and depression. These psychological conditions may adversely affect patients’ quality of life and adherence to long-term treatment. Understanding the prevalence of these conditions at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar is essential to inform appropriate clinical and psychosocial interventions. Objective: This study aimed to describe the prevalence and severity levels of anxiety and depression among patients undergoing hemodialysis at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar. Methods: This descriptive study included 43 patients receiving hemodialysis at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar. Data were obtained from medicalrecords and psychological screening using the digitally administered Hospital Anxiety and Depression Scale (HADS). Anxiety and depression levels were categorized as normal (score 0–7), mild (8–10), moderate (11–14), and severe (15–21). Results: Among the 43 patients, symptoms of anxiety and/or depression were identified in 23.26% (n=10). Of these, 11.63% (n=5) had mild symptoms, 6.98% (n=3) had moderate symptoms, and 4.65% (n=2) had severe symptoms. The remaining 76.74% (n=33) of patients showed no symptoms of anxiety or depression. Conclusion: Anxiety and depression are relatively common among patients undergoing hemodialysis at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar. Routine psychological screening and integration of mental health care into hemodialysis management arestrongly recommended to improve overall patient well-being and quality of life.